THE IMPACT OF SOCIAL INTERACTIONS ON THE STREETS ON URBAN MENTAL HEALTH OF UNIVERSITY STUDENTS IN BANDUNG, INDONESIA - Arifatul Hasanah; Imas Nurrahmah Priandani; Hanson Endra Kusuma (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Brawijaya, 2025)
Urbanization is associated with increased psychological problems among urban dwellers, including university students. Streets, as public social spaces, can play a crucial role in reducing loneliness and improving mental health and resilience. Convivial street interactions, such as meeting strangers, can build social capital, increase community engagement, and enhance social well-being. This research aims to explore university students' perspectives on the streets they frequent daily and the impact of these streets on their mental health. Employing a mixed-methods approach, an online questionnaire with both open- and close-ended questions was distributed to 100 university students in Bandung. Results indicate that 79% of respondents perceive street interactions as positive as enhancing their mood, while 21% view them negatively. Despite this, interactions with strangers on the streets are infrequent. The study finds a significant correlation between street interactions and mental health, with 73% of respondents reporting moderate to high-stress levels linked to low interaction frequency, particularly with vendors/sellers. The poor physical conditions of streets and their primary role as vehicular passageways discourage on-street interactions. The findings underscore the importance of designing streets as